Clinical decision making and outcome in the routine care of people with severe mental illness across Europe (CEDAR) - Puschner, B.; Becker, T.; Mayer, B.; Jordan, H.; Maj, M.; Fiorillo, A.; Égerházi, A.; Ivánka, T.; Munk-Jørgensen, P.; Krogsgaard Bording, M.; Rössler, W.; Kawohl, W.; et al. (Cambridge University Press, 2016)
Aims. There is a lack of knowledge on clinical decision making and its relation to outcome in the routine treatment of people with severe mental illness. This study examined preferred and experienced clinical decision making from the perspectives of patients and staff, and how these affect treatment outcome. Methods. CEDAR (ISRCTN75841675) is a naturalistic prospective observational study with bimonthly assessments during a 12-month observation period. 588 adults with severe mental illness were consecutively recruited from caseloads of community mental health services at the six study sites (Germany, UK, Italy, Hungary, Denmark, and Switzerland). Clinical decision making was measured using two instruments (Clinical Decision Making Style Scale. CDMS;Clinical Decision Making Involvement and Satisfaction Scale, CDIS) from patient and staff perspectives. Outcomes assessed were unmet needs (Camberwell Assessment of Need Short Appraisal Schedule, CANSAS). Mixed-effects multinomial regression was used to examine differences in involvement in and satisfaction with actual decision making. The effect of clinical decision making on outcome was examined using hierarchical linear modelling controlling for covariates. Results. Shared decision making was preferred by patients (2=135.08; p<0.001) and staff (2=368.17; p<0.001). Decision making style of staff significantly affected unmet needs over time, with unmet needs decreasing more in patients whose clinicians preferred active to passive (-0.406 unmet needs per two months, p=0.007) or shared (-0.303 unmet needs per two months, p=0.015) decision making. Conclusions. A shift from shared to active involvement of patients is indicated, including the development and rigorous test of targeted interventions.